Komunikasi dan Sikap Mahasiswa Berhubungan dengan Pencegahan Seks Bebas - Mita Hari Murti; Nutrisia Nu’im Haiya; Iwan Ardian; Intan Rismatul Azizah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Factors contributing to the occurrence of promiscuous sexual behavior include internal and external elements. Internal factors include low self-control, lack of religious understanding, and low sexual knowledge. External factors include family and peers; peer association can influence both positive and negative behaviors. Positive behaviors include participating in beneficial activities with peers, while negative behaviors include violating social norms, such as having casual sex. This research design uses an analytic correlation approach, with the aim of finding the relationship between variables, data collection is done by questionnaire. Using the chi square formula with the help of SPSS, 125 students were asked to answer. The results showed that of the 125 study respondents, most were 21 years old, 36.8 percent, and the majority were female, 58.4%. In addition, the results of the analysis showed that 46% of the respondents showed a good level of knowledge, while 47% showed sufficient attitude and preventive behavior. Conclusion: There is a correlation between knowledge and preventive behavior of promiscuous sex.